Nuclear medicine board review questions and answers for self-assessment - Goldfarb, C. Richard (Thieme, 2012)
"A concise review of all aspects of nuclear medicine, this fully revised second edition includes 1786 questions-and-answers (multiple choice; fill-in-the-blank; and true-or-false) designed to help those preparing for certification or re-certification exams administered by the American Board of Radiology, of which nuclear medicine is an important part. Fully updated with the progress made in the field since the first edition's publication, especially in positron emission tomography (PET)"--Provided by publisher.